Transfer length in full-scale pretensioned concrete beams with 1.4 m and 2.4 m section depths. (15th September 2018) - Yang, Jun-Mo; Kim, Jin-Kook; Yoo, Doo-Yeol
Highlights: Transfer length of newly developed PS strand in full-scale girders is examined. Shorter transfer length is obtained with an increase in section depth. Greater section depth mitigates the effect of detensioning method on transfer length. A conservative use of ACI recommendation (50 db ) is suggested for transfer length prediction of full-scale girders. Abstract: This study aims to investigate the transfer length of full-scale prestressed concrete (PSC) beams with lengths of 30 m and 35 m and section depths of 1.4 m and 2.4 m for highway and railway bridge girders, respectively. To do this, newly developed high-strength ( fpu of 2400 MPa) prestressing (PS) strands were used. The initial and effective prestressing forces applied were 94% of the yield strength and 70% of the ultimate tensile strength of the strands. The difference between the transfer lengths at the cut end and dead end was reduced by increasing the section depth. Greater strains were found at the cut end due to a lateral expansion of the strands by the Hoyer effect compared with those at the dead end, causing a greater stress concentration. The eight most widely used prediction models were adopted to predict the transfer lengths of high-strength PS strands in full-scale PSC beams, and it was found that all models significantly overestimated the transfer lengths. Accordingly, the conservative use of the ACI recommendation of 50 db is suggested based on this study.